Altered expression of aromatase, estrogen receptors and progesterone receptors in human leydig cell hyperplasia - Gonzalez, Candela Rocio (2015)
Testicular function is regulated by pituitary hormones and also by paracrine and autocrine factors. A number of reports have pointed out the importance of estrogens and progesterone in male reproductive tract. Recently, we have reported in testicular biopsies from men with Sertoli Cell Only Syndrome (SCO) or Hypospermatogenesis (H) with Leydig cell hyperplasia (LCH) an increase in the expression of the TGFB1 and its receptors ALK1 and endoglin, which are involved in the proliferation of Leydig cells. The aim of the present work was to analyze the expression of aromatase, estrogen and progesterone receptors (ERs, PR) in pathological testicular biopsies with SCO or H with and without LCH. The ERs and CYP19 proteins were detected in the Leydig cells from all pathological biopsies analyzed. Biopsies with SCO or H with LCH showed an increment in the immunostaining of CYP19 and ERs in the Leydig cells respect to biopsies without LCH. The gene expression of CYP19 was increased in SCO or H biopsies with LCH respect to SCO and H biopsies without LCH. PR was localized in Leydig cells and showed a significant increment in biopsies with LCH respect from biopsies without LCH. The gene expression of both PRA and PRB was increased in biopsies with LCH respect to biopsies without LCH. In concussion, alterations in the gene expression of aromatase, ERs, and PR and the likely interactions of these systems with locally produced factors such as growth factors and cytokines, might lead to Leydig cell proliferation in testicular pathology.